Comparison of Magnetic Resonance Spectroscopy (MRS) data in children with and without HIV at 11-12 years - Graham, Amy (Division of Biomedical Engineering, 2020)
Although HIV and antiretroviral drugs have been shown to cause damage in the brain, the long-term impacts of perinatal infection, early treatment and exposure in children at 11 years, remain unclear. The effects of HIV and antiretroviral therapy (ART), whilst indistinguishable, can be investigated at a chemical level through proton magnetic resonance spectroscopy (1H-MRS). Previous studies in children have largely focused on individual metabolite changes. However, several adult studies have now advanced beyond this to address patterns of metabolic activity that are altered with HIV infection. Using a 3T Skyra scanner, 136 children (76 HIV+, 30 HEU, 30 HU; 71 males) between the ages of 11.0- 12.5 years, and from a similar socioeconomic background, were scanned. In this study metabolite concentrations were quantified within the basal ganglia (BG), midfrontal gray matter (MFGM) and peritrigonal white matter (PWM). We utilised linear regression to investigate individual metabolite differences, comparing HIV-infected (HIV+) children from the Children with HIV Early Antiretroviral Therapy (CHER) trial, and HIV-exposed-uninfected (HEU) children, to HIV-unexposed (HU) children. Pearson's correlation analysis, factor analysis and logistic regression were then used to study alterations in metabolic patterns between HIV+ and HIV-uninfected (HIV-) children. Analysis of the data was carried out in R. We found elevated total choline in the BG (p = 0.03) and MFGM (p < 0.001) of HIV+ children, as well as reduced PWM total NAA (p = 0.03) and total creatine (p = 0.01). Altered metabolite concentrations were further observed in HEU children. Additionally, we identified a cross-regional coupling of choline which distinguishes HIV+ from HIV- children (p < 0.001). These findings indicate that multiregional inflammation and PWM axonal damage are occurring in HIV+ children at 11 years. Ultimately, the consequences of perinatal HIV acquisition, in spite of early treatment, continue to be seen at 11 years, as do the impacts of exposure.